2012
DOI: 10.1074/jbc.m111.333716
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p115-RhoGEF Requires Direct Association of Gα13 and the Dbl Homology Domain

Abstract: Background: p115-RhoGEF can be regulated by activated G␣ 13 . Results: Both RGS and DH domains of p115-RhoGEF interact with G␣ 13 . Conclusion: The binding of RGS to G␣ 13 facilitates direct association of G␣ 13 to DH to regulate its exchange activity. Significance: RGS domains can act cooperatively with other domains to mediate effector regulation by G proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 35 publications
4
32
1
Order By: Relevance
“…GNA13 is a guanine nucleotide binding protein or G protein that is thought to play a role in cell migration through regulation of the exchange activity of RGS-containing RhoGEFs. [30][31][32] We confirmed these observations by knockdown of either CDK2, CyclinA2 (CCNA2) or GNA13 using multiple shRNAs followed by cell proliferation assays in OCIP23 cells in the presence of different concentrations of MK-1775 (Fig. 7C, D, E).…”
Section: Pooled Rna Interference Screen Identifies Genetic Suppressorsupporting
confidence: 67%
“…GNA13 is a guanine nucleotide binding protein or G protein that is thought to play a role in cell migration through regulation of the exchange activity of RGS-containing RhoGEFs. [30][31][32] We confirmed these observations by knockdown of either CDK2, CyclinA2 (CCNA2) or GNA13 using multiple shRNAs followed by cell proliferation assays in OCIP23 cells in the presence of different concentrations of MK-1775 (Fig. 7C, D, E).…”
Section: Pooled Rna Interference Screen Identifies Genetic Suppressorsupporting
confidence: 67%
“…Together, these observations reveal that thrombin modulates cell migration via its PARs that are coupled to various G proteins in different cell types. Some studies have reported that G␣ 12/13 associates with RhoGEFs, such as p115 RhoGEF, involving their RH and DH domains, and enhances their GEF activity (63). It was also reported that the enhancement of the RhoGEF activity by G␣ 12/13 was greater if the RhoGEF is tyrosine-phosphorylated as compared with its nonphosphorylated form (64).…”
Section: Discussionmentioning
confidence: 99%
“…1) and full-length RhoA were inserted into pGEX-KG-TEV either with or without a C-terminal His 6 tag as described previously (10). Mutations were inserted by PCR sewing.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas the RH domain of p115RhoGEF was first characterized as a GAP for the ␣ subunits, it is also necessary for the RhoGEF to mediate direct regulation of RhoA by G protein-coupled receptors that activate G 12 and G 13 (8,9). Recent studies indicate that the main function of the RH domain in activation is to bind and orient the GTPase so that the ␣-helical domain of G␣ 13 can interact effectively, albeit with low affinity, to the back side of the DH domain (10). In a mechanism not yet defined, this interaction stimulates the turnover rate of p115RhoGEF for activation of RhoA.…”
mentioning
confidence: 99%